Bloodstones - Anthony, Evelyn (New York : HarperCollins Publishers, 1994)
A newly discovered mine in Russia's frozen north is yielding rare red diamonds called bloodstones, and Ivan Karakov is about to sign an exclusive agreement with Moscow.
National College of Business and Arts
Keywords: Diamond industry and trade -- Fiction; Detective and mystery fiction